ANALISIS TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA APLIKASI E-LEARNING : (Studi Kasus Pada Mahasiswa Universitas Putra Bangsa) - Alfin Nugroho; Yordan Hermawan Apidana (Journal of Digital Business and Management, 2023)
One of the interesting things to research is how well the use of e-learning as a learning method in higher education. The Technology Acceptance Model (TAM) method is used in this study to evaluate the level of acceptance of e-learning as a learning medium applied in educational institutions. This research is a quantitative research. The population in this study were all students of Universitas Putra Bangsa who had used e-learning-based learning media in lectures. In this study, the sample was taken by purposive sampling. The number of respondents in this study were 100 respondents. Data collection used in this study was by using a questionnaire. While the analysis tool in this research uses multiple regression analysis using SPSS software. Based on data analysis shows that: perceived usefulness has a positive effect on interest in using e-learning, perceived convenience has a positive effect on interest in using e-learning, perceived usefulness and perceived convenience together affect interest in using e-learning. From the results of data analysis in this study, the authors suggest that the Putra Bangsa University institution be able to continue to increase the perception of usefulness and continue to maintain the perception of student ease of use of e-learning learning media.